Neutrosophic Simply b-Open Set in Neutrosophic Topological Spaces - Das, Suman; Tripathy, Binod Chandra (Iraqi Journal of Science, 2021)
In this paper, we procure the notions of neutrosophic simply b-open set, neutrosophic simply b-open cover, and neutrosophic simply b-compactness via neutrosophic topological spaces. Then, we establish some remarks, propositions, and theorems on neutrosophic simplyb-compactness. Further, we furnish some counter examples where the result fails.